Single-cell transcriptomics defines an improved, validated monoculture protocol for differentiation of human iPSC to microglia - Washer, SJ; Perez-Alcantara, M; Chen, Y; Steer, J; James, WS; Trynka, G; Bassett, AR; Cowley, SA (Springer Nature, 2022)
There is increasing genetic evidence for the role of microglia in neurodegenerative diseases, including Alzheimer's, Parkinson's, and motor neuron disease. Therefore, there is a need to generate authentic in vitro models to study human microglial physiology. Various methods have been developed using human induced Pluripotent Stem Cells (iPSC) to generate microglia, however, systematic approaches to identify which media components are actually essential for functional microglia are mostly lacking. Here, we systematically assess medium components, coatings, and growth factors required for iPSC differentiation to microglia. Using single-cell RNA sequencing, qPCR, and functional assays, with validation across two labs, we have identified several medium components from previous protocols that are redundant and do not contribute to microglial identity. We provide an optimised, defined medium which produces both transcriptionally and functionally relevant microglia for modelling microglial physiology in neuroinflammation and for drug discovery.